Another brick in the wall: the EU-India investment-facilitation mechanism - Maria Laura Marceddu (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2019)
This Perspective discusses the idea of an investment facilitation agreement through the lens of bilateral initiatives, with a particular focus on the EU-India investment facilitation mechanism. The author argues that while bilateralism offers a sense of perspective on how far countries are willing to go with an investment facilitation agreement, it does not come without cons.
Keywords: 330